Immunogenicity of protein aldehydes - Li Jovanoska, L (2022)
Protein carbonylation introduces diverse non-enzymatic post-translational modifications (PTMs) containing aldehydes and ketones (reactive carbonyls) during oxidative or glycative stress, and is a hallmark of unhealthy ageing and various neurological, cardiovascular, respiratory, musculoskeletal and metabolic diseases. The activation of innate and adaptive immune responses to carbonylated proteins is thought to trigger or exacerbate these pathologies, although how specific PTMs activate the immune system is not well understood.